Efficacy of a fixed combination of 0.09 % xanthan gum/0.1 % chondroitin sulfate preservative free vs polyethylene glycol/propylene glycol in subjects with dry eye disease: a multicenter randomized controlled trial - Pérez-Balbuena, Ana L.; Ochoa-Tabares, Juan C.; Belalcazar-Rey, Sandra; Urzúa-Salinas, Cristian; Saucedo-Rodríguez, Laura R.; Velasco-Ramos, Regina; Suárez-Sánchez, Raúl G.; Rodríguez-Carrizalez, Adolfo D.; Oregón-Miranda, Aldo A. (BMC ophthalmology, 2016)
Dry eye disease (DED) is multifactorial, affecting 5-34 % of the global adult population and reducing quality of life. The artificial tears or lubricants are the therapy most used for the treatment of DED, due to their low side effect profile, which attempt to modify the properties of the tear film. The aim of the present study was to evaluate the clinical efficacy of a fixed combination of xanthan gum and chondroitin sulfate preservative free on the ocular surface of patients with dry eye disease during 60 days of intervention. A phase III, double-blind, masked, controlled, multicenter, clinical trial of 148 subjects, randomized to either a fixed combination of xanthan gum 0.09 % and chondroitin sulfate 0.1 % (XG/CS) ophthalmic solution (n = 76) or a fixed combination of polyethylene glycol 400 0.4 % and propylene glycol 0.3 % (PEG/PG) (n = 72). Subjects self-dosed four times daily during 60 days. Follow-up was set on days 2, 7, 15, 30 and 60. Assessments of anterior/posterior segment ocular signs were performed. The outcome measures included Schirmer test, tear film break-up time and OSDI score. Security variables included intraocular pressure, lisamine green and fluorescein ocular surface stains. The primary efficacy endpoints were similar between groups at baseline. After intervention time Schirmer test increased in both groups compared to baseline, XG/CS (6.4 ± 2.2 vs 11.0 ± 6.6; p = 0.002) and PEG/PG (6.5 ± 2.5 vs 10.5 ± 5.6; p = 0.019) respectively. Similar results were reported in the tear film break-up time in XG/CS (5.5 ± 2.1 vs 7.4 ± 2.9; p = 0.027) and PEG/PG (5.2 ± 2.0 vs 7.4 ± 2.7; p = 0.046) respectively. The OSDI score decreased to normal values in both groups, XG/CS (19.3 ± 7.4 vs 7.3 ± 5.9; p = 0.001) and PEG/PG (19.3 ± 7.5 vs 7.9 ± 8.2; p = 0.001) respectively. There was no significant difference between treatments for any parameter. Moreover, both groups decreased the presence of burning sensation, tearing, foreign body sensation, conjunctival hyperemia and photophobia. The adverse events were not related to the interventions. Xanthan gum/chondroitin sulfate preservative free showed similar clinical efficacy, evaluated with OSDI score, TBUT and Schirmer test compared to polyethylene glycol/propylene glycol in the treatment of dry eye disease. ClinicalTrials.gov: NCT01657253 . Date of registration May 19, 2014.